Determination of Encapsulated Black Rice Anthocyanins in a Designed Set of Supplementary Products - อรนุช หน่อแก้ว ORRANUCH NORKAEW (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Black rice is broadly known as health-promoting food for its abundance of biologically active compounds. Apart from containing -oryzanols and vitamin E, black rice also contains anthocyanins which are water-soluble pigments responsible for bran color and anti-oxidative property of black rice. However, the stability of these bioactive compounds could be decreased by some post-harvest treatments. One of this research objectives was to investigate the effect of post-harvest treatment on contents of bioactive compounds in black rice. Thai black glutinous rice cv Luem Pua, which contains higher anthocyanins than some other Thai black rice varieties was used as black rice sample in this research. Bioactive compounds including anthocyanins, -oryzanols, and vitamin E in Luem Pua rice were determined using HPLC coupled with PDA, UV/Vis, and FL detectors, respectively. After drying by two methods, sun and hot air drying, Luem Pua paddy samples were divided into two groups. One of them was kept in a cool room (22 C) while the other was in another room under ambient temperature (30 C). Both groups of rice were stored for 10 months. The results showed that drying method, storage temperature, and storage duration affected the contents of these bioactive compounds in Luem Pua rice differently. Sun drying reduced the loss of anthocyanins and -oryzanols more than did hot air drying. Luem Pua rice stored as paddy at cool room retained more anthocyanins, -oryzanols, and vitamin E than did the paddy stored at room temperature. The final contents of anthocyanins, γ-oryzanols, and vitamin E in Luem Pua after 10 months of storage averaged 83.7%, 79.1%, and 54.9% of their original contents, respectively. Anthocyanins in black rice extract have been reported to have a preventive and inhibitive effects on the development of some chronic diseases. However, their bioavailability is low due to their high absorptivity in gastric phase and instability under intestinal digestion. Therefore, another aim of this research was focused on the increase of anthocyanin content under intestinal digestion by encapsulation process. Anthocyanin-rich extract from Luem Pua rice bran was encapsulated by spray drying process at the appropriate inlet air temperature of 180 C. Maltodextrin, gum arabic, whey protein isolate, and their combinations were used as wall materials. The results showed that different wall materials affected the release of anthocyanins and total phenolic compounds from the encapsulated anthocyanin-rich products as well as their anti-oxidant activities. Anthocyanin-rich extract encapsulated with maltodextrin had high total anthocyanin content (6.45 mg/g of product), whereas, encapsulation using whey protein isolate resulted in high total phenolic content (21.60 mg GAE/g of product) and anti-oxidant activity (70.80 µmol trolox/g of product). Simulated gastrointestinal study of encapsulated anthocyanin-rich products exhibited that released anthocyanin and total phenolic contents under intestinal phase of some products were higher than those of non-encapsulated extract. During intestinal digestion, anthocyanin-rich extract encapsulated with whey protein isolate had almost 20% and 25% of released anthocyanin and total phenolic contents, respectively, higher than those of non-encapsulated extract. This product could be applied as supplementary food and it is needed to be stored for a certain period. Effects of packaging and storage duration on anthocyanin and total phenolic contents of encapsulated anthocyanin-rich product was also investigated. The results showed that anthocyanin and total phenolic contents of encapsulated anthocyanin-rich products decreased averagely 27.4% and 13.5%, respectively, after storage for 8 weeks. Encapsulated anthocyanin-rich product packaged in oriented polypropylene pouches had more retained anthocyanins than did those packaged in aluminum pouches.